A heuristic approach of modelling developing countries' construction sector uncertainties to improve the building environment - Pettang Nana, Ursula Joyce Merveilles; Fandjio Yonzou, Cédric Cabral; Mbiada Mbiada, Patrick Joël; Abanda, Fonbeyin Henry; Pettang, Chrispin (Frontiers in Built Environment, 2024)
Building environment is predominated almost everywhere in developing countries by fuzzy and unconventional mechanisms so called “informal sector”. The implementation of projects by the owners themselves, small and medium-sized enterprises in this environment requires harsher costs control and time delivery. The construction process in such a complex area is subject to labour fluctuations, productivity variability, difficulties of logistic supply, poor management, use of unsuitable methods, instability of financial means and therefore delays in the payment of accounts by the contracting authorities. These parameters are source of major discrepancies between the forecast costs, quality, and deadlines and those ending obtained. This explains the losses in the execution phase as well as the prejudices suffered by the main actors in unconventional construction industry at all levels. By comparing this specific construction sector with the standards, specific uncertainties emerge at several levels of understanding and execution, which for each task are the variability of quantity, performance and qualification of workers; the quality and cost fluctuations among supplying networks of materials; the availability and/or inadequacy of equipment used; the improvised managerial and financial mechanisms. This study, based on matrix modelling of the components of the construction site, leads to implement of a heuristic approach for assessing those construction costs and delays uncertainties. We proposed analytic formulations of uncertainties that are computed every iteration of possibles scenarios. By adapting and applying an iterative (TABU Search) a heuristic algorithm for minimising costs and lead times, it is possible to combine virtually all the possible choices for the different variables in order to anticipate the impact and guide the decision-maker towards the scenario with the least uncertainty and good reliability of occurrence. Considering the complex parameters of this site of “informal” construction, the model aims to enable stakeholders in the construction sector to incorporate uncertainties into their forecasts before decisions being taken, not only to reduce or decrease financial losses but also to increase their credibility and ultimately improve this common practice of sustainable construction.